2011
DOI: 10.1007/s00228-011-1060-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of VKORC1 polymorphisms and haplotypes, CYP2C9 genotypes, and clinical factors on warfarin response in Sudanese patients

Abstract: Our data revealed that VKORC1 and CYP2C9 polymorphisms are important factors that influence warfarin dose response in Sudanese patients. Our data suggest that combinations of the SNPs may improve predictions of warfarin dose requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 47 publications
5
33
1
1
Order By: Relevance
“…CYP2C9 *8 (rs9332094) is another rare variant that affects around 12% of African Americans and has been associated with reduced S -warfarin clearance [54]. This SNP was only investigated in two populations of MENA; Egyptians and Sudanese [12, 41]. Despite some of the similarities found between these two populations and African Americans, the CYP2C9*8 did not shown any significant association with warfarin dose requirements in Egyptians and Sudanese as it did in African Americans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CYP2C9 *8 (rs9332094) is another rare variant that affects around 12% of African Americans and has been associated with reduced S -warfarin clearance [54]. This SNP was only investigated in two populations of MENA; Egyptians and Sudanese [12, 41]. Despite some of the similarities found between these two populations and African Americans, the CYP2C9*8 did not shown any significant association with warfarin dose requirements in Egyptians and Sudanese as it did in African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some of the similarities found between these two populations and African Americans, the CYP2C9*8 did not shown any significant association with warfarin dose requirements in Egyptians and Sudanese as it did in African Americans. This might be in part due the fact that this variant was not very common in these populations, it showed a MAF of 0.008 and 0.01 in Egyptians and Sudanese, respectively [12, 41]. On the other hand, the frequencies of CYP2C9 *2 and *3 and VKORC1 (3673G>A) reported in Turkish [43] were closer to Caucasians than to Asians and African Americans [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results, given the smaller range of variant allele frequency for CYP2C9 to that of VKORC1, it is apparent that the association in warfarin therapy stability is larger for VKORC1 than for CYP2C9 29,30 . By taking a general look at the ethnicity versus frequencies of both genes, we found that 22% of all Sudanese patients were without any of the variant alleles of both CYP2C9*2 and VKORC1-1639G>A, that means having neither heterozygous nor homozygous mutant genotypes of the tow genes studied.…”
Section: Genetic and Non-genetic Factors Association With Warfarin Lomentioning
confidence: 95%
“…Overcoagulation causes bleeding episodes, with intracranial hemorrhage being one of the most catastrophic. The effects of genetic polymorphisms in its metabolizing enzyme, CYP2C9, as well as the VKORC1 gene's sensitivity to warfarin have been shown in many studies to significantly affect the dosing requirements [47,48,49,50,51], with the CYP2C9*1/*1 genotype associated with a higher maintenance dose compared to the genotype containing CYP2C9*2 or *3 alleles. There are about 28 known polymorphisms for the VKORC1 gene to date, with the 1639G>A polymorphism being most clinically significant.…”
Section: Cyp2c9 and Vkorc1: Warfarinmentioning
confidence: 99%